Evaluation of PCR-RFLP analysis targeting hsp65 and rpoB genes for the typing of mycobacterial isolates in Malaysia - Ong, Chia Sui; Ngeow, Yun Fong; Yap, Sook Fan; Tay, Sun Tee (Microbiology Society, 2010)
In this study, PCR-RFLP analysis (PRA) targeting hsp65 and rpoB gene regions was evaluated for the identification of mycobacterial species isolated from Malaysian patients. Overall, the hsp65 PRA identified 92.2% of 90 isolates compared to 85.6% by the rpoB PRA. With 47 rapidly growing species, the hsp65 PRA identified fewer (89.4%) species than the rpoB PRA (95.7%), but with 23 slow-growing species the reverse was true (91.3% identification by the hsp65 PRA but only 52.5% by the rpoB PRA). There were 16 isolates with discordant PRA results, which were resolved by 16S rRNA and hsp65 gene sequence analysis. The findings in this study suggest that the hsp65 PRA is more useful than the rpoB PRA for the identification of Mycobacterium species, particularly with the slow-growing members of the genus. In addition, this study reports 5 and 12 novel restriction patterns for inclusion in the hsp65 and rpoB PRA algorithms, respectively.